STEM lecturers’ English language communication practices, ability beliefs, and needs: the case of Saudi universities - Abdel Latif, Muhammad M. M.; Alrashed, Mohammed (Frontiers in Education, 2025)
For internationalization purposes, many higher education institutions in non-English-speaking countries are adopting English as a medium of instruction (EMI) policies. A key challenge is ensuring that subject matter or content teachers possess the required language proficiency levels, as their linguistic readiness is essential for the long-term success and sustainability of Englishization policies, i.e., using English as the language of instruction. This study explored the communication practices, self-perceived language abilities, and needs of 191 STEM lecturers at Saudi universities (n = 61, 58, and 72 lecturers of computer and information technology, engineering, and science majors, respectively). Data were collected through a four-part questionnaire designed to capture insights into the lecturers’ EMI-related experiences and professional development requirements. The one-way ANOVA analyses showed significant differences among the STEM lecturers in their language communication practices, self-perceived language abilities, and needs. The lecturers’ communication practices were closely aligned with their beliefs about their language competence, indicating the link between the perceived English ability and actual language practices in EMI contexts. The science lecturers reported lower confidence in their English abilities and greater communication needs than their peers in the engineering, computer, and information technology majors. These findings underscore the importance of language support. The article concludes by highlighting practical implications for meeting the specific English communication needs of STEM faculty members at Saudi universities.